MEWUJUDKAN PERTANIAN BERWAWASAN LINGKUNGAN - Maryadi Maryadi (Jurnal Teknologi Lingkungan, 2004)
Presently the world is moving away from inorganic fertilizer, weed and pest control. As we know in many countries rice paddies are fertilized with inorganic fertilizer and sprayed with pesticides as a way to control weeds and other pests. This process, however, is harmful to the people, animal and plant life in the surrounding area. The use of Azolla pinata as green manure and source of nitrogen may can be used to reduce the use of inorganic fertilizer.